Income Inequality and Stock Market Returns - Agnieszka Markiewicz; Rafal Raciborski (Tinbergen Institute, 2018)
In this paper, we study the relationship between income inequality and stock market returns. We develop a quantitative general equilibrium model that links shifts in both labour and capital income inequality to stock market variables. An increase of the share of capital owners' income from risky capital leads to higher equity premium and a rise in their non-risky, labor share of income reduces it. When we calibrate our model to match the empirical size of shifts in the last five decades, we find that the negative impact of the higher labour share of income of capital owners dominates and brings the equity premium below the historical value by 0.79 percentage points, in line with the data. If both capital and total income shares of top decile would continue growing at the historical rate between 1970 and 2014, the equity premium would continue decreasing to 6.11% in 2030, 0.92 percentage point lower than historical equity premium of 7.03%. If instead only the capital share of income continues to grow, the equity premium would be higher than the historical average by 0.57 percentage point. If the labour income dispersion remains constant, the historical equity premium of 7.03% would be reached by 2030 if the capital share of income was growing by 1.4% each year.
Keywords: D31; E32; E44; H21; O33; 330; Asset Pricing; Risk Premium Dynamics; Income Inequality; Computational Macroeconomics